VARIASI GENETIK UJI PROVENAN MERBAU SAMPAI UMUR 3 TAHUN DI BONDOWOSO, JAWA TIMUR - Tri Pamungkas Yudohartono; Burhan Ismail (Jurnal Pemuliaan Tanaman Hutan, 2012)
Merbau (Intsia bijuga) is one of high economic value timbers. Establishment of seed source of merbau is essential tosupply qualified seeds for plantation. Center for Forest Biotechnology and Tree Improvement has established provenance test of merbau at Sumberwringin Research Forest in Bondowoso, East Java. The objectives of this study are to know survival and genetic variation of growth traits in provenance test plot of merbau. This provenance test was designed as Randomized Complete Block Design with single factor of provenance consisted of Halmahera Timur, Waigo, Oransbari, Wasior, Nabire and Seram. Each provenance comprises 3 blocks as replication and 60 treeplots of each block. The result showed high survival rate of all provenances (above 90 %). Moreover, genetic variation of height and stem diameter among provenances was also high. The best provenance for survival, and height for all observation years was Wasior. The best provenance for diameter for all observation years was Halmahera Timur. Meanwhile, provenance having the best value of survival, height and diameter for all observation years was Halmahera Timur. The  provenance having the worst value of height and diameter for all observation years was Seram. Whereas, the worst provenance of survival at 1, 2 and 3 years old were Waigo, Halmahera Timur dan Seram, respectively.